La traduction en polonais des textes d'ancien français: une compétence spécifique - Giermak-Zielińska, Teresa (Studia Romanica Posnaniensia, 2003)
This paper is relating a practical experience of teaching Romance philology students the translation from ancient French into Polish. The main scope is a restitution of an ancient text respecting not only the equivalence at the Iexical and syntactical level, but also the discourse structures, such as the linear sequence of events and events related from different points of view: some examples of solving particular problems are discussed. The whole procedure resembles that of translating from Latin, rather than a translation from one modern language to another.